Clinical management of temporomandibular disorders: controlling bruxism and temporomandibular joint load Penanganan klinis gangguan temporomandibula: pengendalian bruksisma dan beban sendi temporomandibula - Shogo Minagi (DiscoverSys Inc., 2011)
The first step of clinical management of the temporomandibular disorders (TMD)is to distinguish the origin ofproblem, to classify into myogeneous and joint problems, which have been regarded to be an important process.Although the precise mechanisms for the symptoms or pathology of these conditions have not yet been clarified,muscular parafunction or hyperfunction has been regarded to play an important role in the etiology of TMD. Excessmechanical loading to the temporomandibular joint (TMJ) has been reported to be one of the possible causes for thedevelopment of osteoarthritis. These forces might be exerted through mandibular parafunctions like sleep bruxism ortooth contacting habit. For clinical control of sleep bruxism, a thick palatal appliance which fills the palate and doesnot cover the occlusal surface have been developed. In this review article, clinical implication of the relationshipbetween occlusion, mastication and bruxism have also been discussed.